2014
DOI: 10.1631/jzus.a1400159
|View full text |Cite
|
Sign up to set email alerts
|

Random amplified polymorphic DNA reveals that TiO2 nanoparticles are genotoxic to Cucurbita pepo

Abstract: Titanium dioxide nanoparticles (TiO 2 NPs) are used in cosmetics, sunscreens, paints, and toothpaste, among other applications. These NPs are very stable and can be transported and dispersed in wastewater and biosolids. Animal species have shown negative reactions to TiO 2 NPs. However, little is known about their toxicity in plants, specifically the possibility of genotoxic effects. In this study, we used a random amplified polymorphic DNA (RAPD) technique to study the genotoxic effects of TiO 2 NPs on hydrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 24 publications
1
12
1
Order By: Relevance
“…This is in contrast to Moreno-Olivas et al (2014) who observed n TiO 2 -induced genotoxicity in hydroponically cultivated zucchini. As the size of n TiO 2 they reported is comparable to that used in our work, the different results obtained can be explained by (i) the different cultivation systems (Petri dishes vs. full nutrient solution in hydroponics) and (ii) the n TiO 2 concentration used by Moreno-Olivas et al (2014 ; 10-fold smaller). The latter potentially prevents the formation of big NP agglomerates, making them more bioavailable.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to Moreno-Olivas et al (2014) who observed n TiO 2 -induced genotoxicity in hydroponically cultivated zucchini. As the size of n TiO 2 they reported is comparable to that used in our work, the different results obtained can be explained by (i) the different cultivation systems (Petri dishes vs. full nutrient solution in hydroponics) and (ii) the n TiO 2 concentration used by Moreno-Olivas et al (2014 ; 10-fold smaller). The latter potentially prevents the formation of big NP agglomerates, making them more bioavailable.…”
Section: Discussioncontrasting
confidence: 99%
“…48 - 50 Yusefi-Tanha et al 51 found that small sized CuO nanoparticles (25 nm diameter) were more phytotoxic than large sized CuO nanoparticles (50 nm and 250 nm) to Soybean. Moreno-Olivas et al 52 reported that nanoparticles interaction with plant cell could lead to change in plant genes expression. Higher concentration of nanoparticles is toxic to plants as López-Moreno et al 53 reported that high dose of CeO 2 nanoparticles damaged the DNA structure in soybean.…”
Section: Discussionmentioning
confidence: 99%
“…RAPD has been used to confirm the genotoxic effect of ZnO and CuO NP on buckwheat ( Fagopyrum esculentum ) seedlings ( Comrey and Lee, 2013 ). Additionally, RAPD analysis of zucchini ( C. pepo ) plants treated with TiO 2 NP exhibited DNA changes compared to the control plants ( Moreno-Olivas et al, 2014 ). Genotoxicity of CeO 2 and ZnO NP on soybean seedlings was demonstrated by the appearance of new DNA bands through RAPD analysis by López-Moreno et al (2010) .…”
Section: Discussionmentioning
confidence: 99%